Use of Aqueous Humor and Flow Cytometry in Ocular Sarcoidosis Diagnosis. (4th July 2017) - Oleñik, Andrea; Gonzalo-Suárez, Beatriz; Revenga, Marcelino; Roldán, Ernesto; Vázquez, Mónica; Muñoz-Negrete, Francisco J.
ABSTRACT: Purpose : To report the use of flow cytometry on aqueous fluid to diagnose sarcoidosis in a patient with recurrent granulomatous anterior uveitis. Methods : Case report. Results : Flow cytometry on aqueous fluid demonstrated a CD4/CD8 ratio >9.5, consistent with a diagnosis of sarcoidosis. Conclusions : Flow cytometry on aqueous fluid may offer an additional pathway for diagnosing sarcoid anterior uveitis.